Book Review - Urban Environmental Sustainability: Liveable Cities, Nigeria - Sule Abass Iyanda (Journal of Architecture, Planning and Construction Management, 2020)
The book is a collection of original researches that discussed various environmental challenges and proffer solutions to the environmental challenges in Nigeria based on empirical studies carried out by various contributors. The central theme of the book explores the concepts of liveability and sustainability as the overall goal of urban design. â€œurban designâ€ is referred to as a place making for people and it fosters sustainable environment-behaviour relationships. In the process of making especially in the â€œcontemporary city development and in the built-environment in generalâ€ (p.9), the professionals in all related disciplines have to work together in a â€˜common spaceâ€™ in order to realise the vision of good quality environment. Hence, articles in the book cut-across various disciplines and the research approaches are inter-disciplinary and multidisciplinary in nature. The book is divided into twenty-one chapters.